Upscaling energy concentration in multifrequency single-bubble sonoluminescence with strongly degassed sulfuric acid - Rosselló, Juan Manuel (2012)
Single-bubble sonoluminescence (SBSL) was explored under a variety of multifrequency excitations. In particular, biharmonic excitation was used to produce SBSL for unprecedented low dissolved noble gas concentrations in a sulfuric acid solution. Reducing the amount of dissolved noble gas makes it possible to reach higher acoustic pressures on the SL bubble, which otherwise are not attainable because of the Bjerknes instability. By using biharmonic excitation, we were able to experimentally trap and to spatially stabilize SL bubbles for xenon pressure overhead as low as 1 mbar. As a result, we have access to regions in phase space where the plasma temperatures are higher than the ones reached before for bubbles driven at ≈30 kHz.